The Influence of Factors on Individual Work Performance: A Conceptual Model - Zuhroh, Nur Fatimatuz (BIMA : Journal of Business and Innovation Management, 2024)
The demands for digital transformation in the current digitalization era make it necessary for organizations or companies to be able to solve problems that can suddenly arise, especially in the Covid-19 era, because of this, a leader is required to be able to have quantity in solving existing problems, which also brings influence on individual performance achievements in an organization. This research was conducted to formulate and design a conceptual model for analyzing the impact of individual work performance in organizations. Several other factors were also developed in research, namely leadership and individual characteristics in an organization. This research uses a conceptual framework, where the theoretical basis is identified by input in the form of task leadership and relationships, processes in the form of individual behavior and affectivity, and output in the form of individual performance. Quantitative research methods using SEM-PLS can be used in processing this research data so that the results of the conceptual framework can be identified as findings in future research. The limitation of this research is that it is still in the conceptual model formulation stage so further research is needed in processing the data so that the findings can be verified.